Semantic annotations similarity measure to compare processes profiles - Шевченко, Олена Леонідівна (Eastern-European Journal of Enterprise Technologies, 2013)
Improved method to calculate similarity measure for semantic ontological graph annotations is introduced in the article. Nodes of such a graph are concepts of problem area ontology and edges – relations among them. The method proposed can be used to improve synthesis of structural procedural program schemas based on semantic computing networks. Improved synthesis method takes into account not only computation relations among network components but their semantic annotation, that formalizes the aim of the software component. By integrating such semantic annotations ontology into top level OWL-S ontology one can use introduced metric to discover or recommend web-service by their detailed profile and user’s request